Evaluation of shrinkage and weld line strength on thick flat part in injection moulding process
Mechanical properties such as strength of moulded part is critical predominantly for parts that require a sufficient strength for the functionality of the product. One of the main concerns that affects the mechanical properties is weld line defect which occurs when two or more gates are used during the injection moulding process. In addition, the dimensions of the part are also crucial in terms of precision of the product. Thus, the shrinkage of the moulded parts also needs to be controlled. Most of the previous studies focus on the weld line strength or the shrinkage of the moulded part separately and it is rare to find studies that incorporate both of these aspects. Therefore, the current study evaluates both shrinkage and strength of weld line using Design of Experiment (DOE) and Response Surface Methodology (RSM) in multi-objectives optimisation utilizing the injection moulding parameters. The mould was successfully designed and fabricated complete with gating system, cooling system, core and cavity of a thick flat part based on ISO standard. The variable parameters used in this study are coolant inlet temperature, melt temperature, packing pressure and cooling time. Simulation process was conducted to determine the recommended setting of injection moulding parameters and the range of the variable parameters. The acceptable range of coolant inlet temperature was set between 50°C and 70°C, while the melt temperature was between 250°C and 270°C. The range of packing pressure was set between 50 MPa to 70 MPa and cooling time between 8 s and 12 s. Experimental works were conducted according to the experimental design where regression models were established to predict the shrinkage and weld line strength. An optimal setting parameter of the process was established to achieve the optimum shrinkage and weld line strength of the moulded part. The results of shrinkage and weld line strength using an optimal setting after optimisation process were compared with the results obtained using the recommended setting. It was found that, the shrinkage in the normal and parallel directions to the melt flow were reduced by 5.97 % and 4.91 % by predicted model generated using RSM. On the other hand, the weld line strength was improved by 3.76 % as compared to the weld line strength obtained from the recommended setting.